Produktivitas Puyuh yang Diberi Ransum Suplementasi Berbagai Level Tepung Cangkang Telur Itik - Gilang Rafi Abyansyah; Suhardi Suhardi; Eudia Christina Wulandari (Tropical Animal Science, 2020)
This study aims to determine the extent of the effect from different levels of supplementation of duck egg shells powder in the diet of quail (Coturnix-Coturnix japonica) as feed material source of calcium to productivity quail. This study used 82 birds 49 days old female quail and retrieval of data up to the age of 90 days. The experimental design used completely randomized design (CRD), which consists of 4 treatments and 5 replications. Such treatment is a duck egg shell powder with some level of rationing, ie P0 = 0% duck egg shell powder, P1 = 0.25% duck egg shell powder + 99.75% commercial feed, P2 = 0.50% duck egg shell powder + 99.5% commercial feed, P3 = 0.75% duck egg shell powder + 99.25% commercial feed. The measured parameters ie feed consumption, calcium, protein, and the daily egg production (QDP). ANOVA test results stating that the treatment significantly different (P>0,05) on daily egg production (QDP) and very significantly different (P>0,01) on egg weights. Based on the results of this study indicate that duck egg shell powder at 0.5% can be used optimally to affect the daily egg production of quail and at 0,25% can be used to affect the egg weights.